Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Education; Electric Power; Manufacturing Materials An 2010
DOI: 10.1115/gt2010-23221
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study on the Effect of Angles of Attack on a Double-Cone Type Supersonic Inlet With Bleeding System

Abstract: The flow characteristics on a supersonic inlet with bleeding system at various angles of attack are studied by using computational 3D turbulent flow analysis. A turbulent CSCM compressible upwind flux difference splitting Navier-Stokes method with k-w turbulence model is used to compute the inlet flowfields. MPICH-2.0 library and PC-cluster system are used to reduce computational times. Distortion and average of total pressure recovery at the AIP (aerodynamic interface plane) are used as evaluation criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was of interest to identify effects of a fixed geometry bleed on the intake performance at off-design conditions including different free stream Mach numbers and angles of attack in some investigations. 21,[57][58][59] According to these studies, even a fixed geometry bleed has beneficial effects on the intake performance at off-design conditions as seen from Figures 22 and 23. However, experimental studies of Soltani et al 21 showed that for M 1 ¼ 1.8, using the bleed at off-design condition may result in destructive effects for some special cases (Figure 24).…”
Section: Effectiveness Of the Bleed At Off-design Conditionsmentioning
confidence: 99%
“…It was of interest to identify effects of a fixed geometry bleed on the intake performance at off-design conditions including different free stream Mach numbers and angles of attack in some investigations. 21,[57][58][59] According to these studies, even a fixed geometry bleed has beneficial effects on the intake performance at off-design conditions as seen from Figures 22 and 23. However, experimental studies of Soltani et al 21 showed that for M 1 ¼ 1.8, using the bleed at off-design condition may result in destructive effects for some special cases (Figure 24).…”
Section: Effectiveness Of the Bleed At Off-design Conditionsmentioning
confidence: 99%
“…For example, large regions of laminar flow for an aircraft can be realized in flight using slotsuction laminar flow control, leading to a pronounced reduction in drag and a remarkable improvement in fuel efficiency [3]. For transonic wings and supersonic inlets, the overall performance is significantly affected by the presence of shock wave-boundary layer interactions (SWBLIs) and boundary layer bleed can be used to reduce the adverse effects of SWBLIs [4][5][6][7]. At wind tunnels, bleed slots can be employed to maintain a laminar boundary layer on the nozzle wall and avoid acoustic fluctuations generated by boundary layer turbulence, further replicating the low noise conditions of actual flight [8].…”
Section: Introductionmentioning
confidence: 99%